Dysuria Following Stereotactic Body Radiation Therapy for Prostate Cancer - Janowski, Einsley-Marie; Kole, Thomas P.; Chen, Leonard N.; Kim, Joy S.; Yung, Thomas M.; Collins, Brian Timothy; Suy, Simeng; Lynch, John H.; Dritschilo, Anatoly; Collins, Sean P. (Frontiers in Oncology, 2015)
Background: Dysuria following prostate radiation therapy is a common toxicity that adversely affects patients’ quality of life and may be difficult to manage. Methods: 204 patients treated with stereotactic body radiation therapy (SBRT) from 2007 to 2010 for localized prostate carcinoma with a minimum follow up of three years were included in this retrospective review of prospectively collected data. All patients were treated to 35-36.25Gy in 5 fractions delivered with robotic SBRT with real time fiducial tracking. Dysuria and other lower urinary tract symptoms were assessed via Question 4b (Pain or burning on urination) of the Expanded Prostate Index Composite (EPIC)-26 and the American Urological Association (AUA) Symptom Score at baseline and at routine follow up. Results: 204 patients (82 low-, 105 intermediate-, and 17 high risk according to the D’Amico classification) at a median age of 69 years (range 48-91) received SBRT for their localized prostate cancer with a median follow up of 47 months. Bother associated with dysuria significantly increased from a baseline of 12% to a maximum of 43% at one month (p<0.0001). There were two distinct peaks of moderate to severe dysuria bother at 1 month and at 6-12 months, with 9% of patients experiencing a late transient dysuria flare. While a low level of dysuria was seen through the first two years of follow-up, it returned to below baseline by two years (p=0.91). The median baseline AUA score of 7.5 significantly increased to 11 at 1 month (p<0.0001) and returned to 7 at 3 months (p= 0.54). Patients with dysuria had a statistically higher AUA score at baseline and at all follow-ups up to 30 months. Dysuria significantly correlated with dose and AUA score on multivariate analysis. Frequency and strain significantly correlated with dysuria on stepwise multivariate analysis. Conclusions: The rate and severity of dysuria following SBRT is comparable to patients treated with other radiation modalities.